Symbiotic bacteria in the relationship between Anaphes nitens (Hymenoptera: Mymaridae) and Gonipterus platensis (Coleoptera: Curculionidae) - Ribeiro, Murilo Fonseca [UNESP]; Carvalho, Vanessa Rafaela [UNESP]; Favoreto, Ana Laura [UNESP]; de Marchi, Bruno Rossitto; Bello, Vinicius H. [UNESP]; Jordan, Carolina [UNESP]; Soliman, Everton Pires; Zanuncio, José Cola; Sabattini, Julian Alberto; Wilcken, Carlos Frederico [UNESP] (Wiley, 2023)
The egg parasitoid Anaphes nitens (Hymenoptera: Mymaridae) parasitizes the Eucalyptus snout-beetle Gonipterus platensis (Coleoptera: Curculionidae), one of the main defoliating beetles of Eucalyptus. Outbreaks of this pest are being recorded in areas with low parasitism rates by A. nitens. Endosymbiont bacteria can affect the reproductive characteristics of host insects increasing or decreasing the parasitism rate. The objectives of this study were to identify the presence, phylogeny and transmission modes of endosymbiont bacteria in A. nitens and G. platensis. Six populations of A. nitens and one of G. platensis were evaluated. Genomic DNA from these populations was extracted and nine genera of cell endosymbionts were searched by PCR. Three species of the Enterobacteriaceae family, Erwinia amylovora, Serratia grimesii, Yersinia massiliensis and the cell endosymbiont Rickettsia belli were identified in all A. nitens populations. Only Serratia grimesii was found in G. platensis. The presence of E. amylovora, Y. massiliensis and R. belli in the F1 and F2 generations indicates vertical transmission in A. nitens, while S. grimesii is vertically transmitted in G. platensis.
Keywords: Eucalyptus; forest entomology; parasitoid; vertical transmission